Pelaksanaan Bimbingan Pranikah Pada Penyuluh di KUA dalam Mengurangi Pernikahan Dini Pada Remaja - Sasmita, Karti; Zhila Jannati; Bela Janare Putra (Social Science and Contemporary Issues Journal, 2024)
This research is entitled "Implementation of premarital guidance by counselors at KUA in reducing early marriage among teenagers". Early marriage is a marriage that occurs when a person is still an adult, has not yet entered adulthood, or has just passed that period.This research is qualitative research using descriptive methods. Implementation of premarital guidance for counselors includes steps to overcome this, analysis is carried out using an inductive approach, which produces general conclusions from specific cases. Data collection techniques used include observation, interviews and documentation methods. The data analysis method applied is based on the Miles and Hubermen approach, which states that activities in data analysis include the process of condensing data, presenting data, and drawing conclusions.The results of this research show that before the implementation of premarital guidance, Karang Gede Village still experienced quite high levels of early marriage. Data shows that many teenagers marry before reaching the target age of adulthood, their readiness is not optimal, they are still unstable, they cannot control their emotions due to various social, economic and cultural factors. Description of the implementation of premarital guidance for counselors at KUA in reducing early marriage among teenagers based on the results of research conducted on counselors at KUA. Premarital Guidance is a way of helping individuals.With the aim of reducing early marriage among teenagers through providing assistance and information. Where premarital guidance is carried out once a month according to KUA's busy schedule, by providing a lecture method focused on unmarried teenagers to motivate them to take part in premarital guidance. The important elements of premarital guidance services provided at KUA include giving lectures, implementing programs, providing material about early marriage overview after premarital guidance After the premarital guidance program,There has been a significant decline in the rate of early marriage. The education provided by KUA counselors includes the significance of mental, emotional and financial readiness before marriage, as well as the risks that arise from marrying at a young age.